Sosialisasi Permainan Tradisional Gen-Z dalam Menerapkan Nilai-Nilai Budaya Lokal di SD Negeri Bukit Rata Aceh Tamiang: Pengabdian - Zuraini Zuraini; Rahmi Hayati; Eli Nofriati; Riszky Anandawar (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service activity aims to socialize traditional games to Generation Z students in order to instill local cultural values at SD Negeri Bukit Rata, Aceh Tamiang. The development of digital technology causes children to interact more often with gadgets, so their involvement in traditional games is decreasing. In fact, traditional games have an important function in training social skills, motor skills, and instilling character values such as cooperation, sportsmanship, discipline, and mutual cooperation. This service program was carried out through several stages, namely observation, counseling, game demonstration, hands-on practice, and evaluation. The games introduced included cricket, gobak sodor, and tug of war. The results of the activity showed high enthusiasm from the students as well as an increase in their understanding of the local cultural values contained in the game. In addition, students became more physically active and more involved in positive social interactions. Teachersalso responded positively by stating that traditional games can be used as an alternative learning activity that is fun and educational. Thus, this activity is effective in supporting efforts to preserve local culture through an educational approach that suits thecharacteristics of Generation Z students.